Uji CBR Terendam Pada Tanah Pasir Yang Distabilisasi Dengan Aspal Cair 60 - 70 - Abdul Ajid (Jurusan T.Sipil Fakultas Teknik UMY, 2013)
Uji CBR Terendam Pada Tanah Pasir Yang Distabilisasi Dengan Aspal Cair 60 - 70